The Influence of Financial Literacy and Financial Attitude on Financial Management Behavior with Locus of Control as an Intervening Variable in Dupa Harum Jaya Perdana Small and Medium Industry Employees - Sri Ayuni, Ni Made; Prayoga, I Putu Duta; Dewi, Mertyani Sari; Sri Kasih, Ni Luh (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study aims to examine the effect of Financial Literacy and Financial Attitude on Financial Management Behavior, with Locus of Control as an intervening variable among employees of the Small and Medium Industry Dupa Harum Jaya Perdana. The research employs a quantitative approach, using a questionnaire distributed directly to respondents, specifically the 32 employees of IKM Dupa Harum Jaya Perdana, and utilizing a Likert scale for measurement. The data analysis technique used is Structural Equation Modeling based on Partial Least Squares with the SmartPLS application. The results of this study indicate that Financial Literacy has a positive and significant effect on Financial Management Behavior, Financial Attitude has a positive and significant effect on Financial Management Behavior, and Locus of Control has a positive and significant effect on Financial Management Behavior. Additionally, Financial Literacy has a positive and significant effect on Locus of Control, and Financial Attitude has a positive and significant effect on Locus of Control. However, Financial Literacy through Locus of Control has a positive but not significant effect on Financial Management Behavior, and Financial Attitude through Locus of Control also has a positive but not significant effect on Financial Management Behavior.